Critical Analysis of Rasa Ratna Samuchhaya with Respect to its Applied Aspects on Ayurvedic Pharmaceutical Process - Sudhaldev Mohapatra; Sanjay Aggarwal; Anupam Srivastav (Wolters Kluwer Medknow Publications, 2024)
Objective:Rasa Ratna Samuchaya is one of the pioneer literature of Rasa Shastra, written during 13th Cen. AD. Acharya Rasa Vagbhat has written this book with utmost care to the practical and applied aspects of Ayurvedic pharmaceutics in the ancient language. The objective of this review article is to explore and critically analyze the trend of development and applied aspects of Ayurvedic pharmaceutics in contemporary language that may help the academicians and Ayurveda industries.Data Sources:The current manuscript is prepared collecting literature from the book Rasa Ratna Samuchhaya, different commentary on it by eminent scholars and from published papers in different journals.Review Methods:The facts and philosophies mentioned in the same book and different commentaries are thoroughly analyzed, reviewed with respect to historical edges, traditional values, and applied aspects and tried to present systematically and affirmatively.Conclusion:The concerned part of the book reviewed is the 11 chapters, of the first part of the book, where the author has tried to describe; the definition of technical terminologies, designing and uses of different types of tools and devices, identification and collection of materials, systematic pharmaceutical processings, and therapeutic uses as well, in concern with metals/minerals. This book acknowledges all the fundamental principles of Rasa Shastra systematically with approaching its future course of development. This manuscript contains all the rational and time needed descriptions with the elimination of impractical and outdated hypothetical materials (carry forwarded by many previous era authors), having no more utility, with the use of available materials and contemporary intellectuals.